FPGA Based a PWM Technique for Permanent Magnet AC Motor Drives - Tole Sutikno; Nik Rumzi Nik Idris; Nuryono Satya Widodo; Auzani Jidin (Institute of Advanced Engineering and Science, 2012)
The permanent magnet AC motor trapezoidal (BLDC motor) is not strictly DC motor, which uses a pulsed DC fed to the stator field windings to create a rotating magnetic field. Therefore, the motor needs an electronic commutation to provide the rotating field. A pair of switches must be turned on sequentially in the correct order to energize a pair of windings. If the incorrect order is applied, then the BLDC motor will not operate properly. This paper presents a smart guideline to ensure that the order to energize a pair of windings is correct. To ensure the guideline, FPGA based a simple commutation state machine scheme to control BLDC motor is presented. The experiment results have shown that the guideline is correct. The commutation scheme was successfully realized using Altera's APEX20KE FPGA to control BLDC motor in both of forward/reverse rotations or forward/reverse regenerative braking properly.